Credit Line Usage, Checking Account Activity, and Default Risk of Bank Borrowers - Norden, Lars; Weber, Martin (Review of Financial Studies, 2010)
[Information on borrower quality is a fundamental issue in debt contracting, corporate and consumer finance, and financial intermediation. We investigate the link between account activity and information production on borrower risk. Based on a unique data set, we find that credit line usage, limit violations, and cash inflows exhibit abnormal patterns approximately 12 months before default events. Measures of account activity substantially improve default predictions and are especially helpful for monitoring small businesses and individuals. Furthermore, early warning indications result in higher loan spreads, and in a higher likelihood of limit reductions and complete write-offs. Our study shows that account activity provides a real-time window into the borrower's cash flows, thus explaining why banks have an advantage in providing certain types of debt financing.]